2010
DOI: 10.1128/aac.01489-09
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae Clinical Isolates with Plasmid pB1000 Bearing bla ROB-1 : Fitness Cost and Interspecies Dissemination

Abstract: Plasmid pB1000 is a mobilizable replicon bearing the bla ROB-1 ␤-lactamase gene that we have recently described in Haemophilus parasuis and Pasteurella multocida animal isolates. Here we report the presence of pB1000 and a derivative plasmid, pB1000, in four Haemophilus influenzae clinical isolates of human origin. Pulsed-field gel electrophoresis showed unrelated patterns in all strains, indicating that the existence of pB1000 in H. influenzae isolates is not the consequence of clonal dissemination. The repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 27 publications
3
50
0
Order By: Relevance
“…2h). The competitive disadvantage of plasmid pB1000 on H. influenzae strain Rd found in this study is in agreement with that reported by San Millan et al (2010). In contrast, the three TEM-1-bearing plasmids were differentially tolerated by the two bacterial hosts: pPN223 and pA1606 did not impose a significant fitness cost to H. influenzae strain Rd, and pA1209 did not impose a significant fitness cost to H. parainfluenzae strain HK 23, while the reverse combinations resulted in significant disadvantages (Fig.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…2h). The competitive disadvantage of plasmid pB1000 on H. influenzae strain Rd found in this study is in agreement with that reported by San Millan et al (2010). In contrast, the three TEM-1-bearing plasmids were differentially tolerated by the two bacterial hosts: pPN223 and pA1606 did not impose a significant fitness cost to H. influenzae strain Rd, and pA1209 did not impose a significant fitness cost to H. parainfluenzae strain HK 23, while the reverse combinations resulted in significant disadvantages (Fig.…”
Section: Resultssupporting
confidence: 83%
“…Small beta-lactamase bearing plasmids were isolated from strains of H. influenzae (pPN223, pA1209 and pA1606) (Søndergaard et al, 2012) or H. parainfluenzae (pSF3) (Tristram et al, 2008). Plasmid pB1000 was kindly donated by Professor Bruno Gonzales-Zorn (San Millan et al, 2010). The bla TEM-1 plasmids used in this study represent each of the three TEM-1-bearing small plasmid types hitherto characterized in H. influenzae.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the antibiotic resistance genes, a few of these plasmids have also been found to carry genes with other functions, such as plasmid mobilization, segregation, or replication genes (522) and putative cation transporter genes (80,532). Many of the plasmids carrying antibiotic resistance determinants are transferrable among the Pasteurellaceae members, as well as other Gram-negative bacteria (517,518,522,529,(533)(534)(535)(536).…”
Section: Antibiotic Resistancementioning
confidence: 99%